Martyniaceae and Sonneratiaceae in Nepal - Dahal, Sajan (Journal of Plant Resources, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Two flowering plant families, Martyniaceae and Sonneratiaceae, each having one genus and one species in Nepal, are described. Bulletin of the Department of Plant Resources Vol 30, 2008 pp 68-70